Autologous Mesenchymal Stem Cells Increase Cortical Perfusion in Renovascular Disease - Saad, Ahmed; Dietz, Allan B.; Herrmann, Sandra M.S.; Hickson, LaTonya J.; Glockner, James F.; McKusick, Michael A.; Misra, Sanjay; Bjarnason, Haraldur; Armstrong, Adam S.; Gastineau, Dennis A.; Lerman, Lilach O.; Textor, Stephen C. (Journal of the American Society of Nephrology, 2017)
Atherosclerotic renovascular disease (RVD) reduces renal blood flow (RBF) and GFR and accelerates poststenotic kidney (STK) tissue injury. Preclinical studies indicate that mesenchymal stem cells (MSCs) can stimulate angiogenesis and modify immune function in experimental RVD. We assessed the safety and efficacy of adding intra-arterial autologous adipose-derived MSCs into STK to standardized medical treatment in human subjects without revascularization. The intervention group ( n =14) received a single infusion of MSC (1.0 × 10 5 or 2.5 × 10 5 cells/kg; n =7 each) plus standardized medical treatment; the medical treatment only group ( n =14) included subjects matched for age, kidney function, and stenosis severity. We measured cortical and medullary volumes, perfusion, and RBF using multidetector computed tomography. We assessed tissue oxygenation by blood oxygen level–dependent MRI and GFR by iothalamate clearance. MSC infusions were well tolerated. Three months after infusion, cortical perfusion and RBF rose in the STK (151.8–185.5 ml/min, P =0.01); contralateral kidney RBF increased (212.7–271.8 ml/min, P =0.01); and STK renal hypoxia (percentage of the whole kidney with R2*>30/s) decreased (12.1% [interquartile range, 3.3%–17.8%] to 6.8% [interquartile range, 1.8%–12.9%], P =0.04). No changes in RBF occurred in medical treatment only subjects. Single-kidney GFR remained stable after MSC but fell in the medical treatment only group (−3% versus −24%, P =0.04). This first-in-man dose-escalation study provides evidence of safety of intra-arterial infusion of autologous MSCs in patients with RVD. MSC infusion without main renal artery revascularization associated with increased renal tissue oxygenation and cortical blood flow.